Cerium oxide nanoparticles in agroecosystems: stage-dependent impacts on sorghum growth, forage quality, bioenergy composition, and environmental risk - Linlin Mu; Mahsa Ghorbani; Fatemeh Ganjalikhan Hakemi; Zohreh Ranjbar; Caroline Korte; Bradley Rauh; Gongde Chen; Haizhou Liu; William Bridges; Stephen Kresovich; Christophe J.G. Darnault (Total Environment Advances, 2026)

Coastal land reclamation induced estuarine nutrient-related eutrophication stressors: phenomena, evaluation and management strategies - Linlin Wang; Yuehua Guo; Wenbin Liu; Huaihao Shao; Shuangliang Dai; Lin Mu; Xianzhong Mao; Hongsheng Bi; Kai Zhou; Xiaoyu Lei (Journal of Hydrology, 2026)

HDC-Net: A hierarchical detection and counting framework for apple aphids with density-level classification - Bo Ma; Zhuo Ren; Shuangxi Liu; Linlin Sun; Junlin Mu; Qiaolin Chen; Jiawei Xu; Rongsen Xie; Xianliang Hu; Yongqiang Zheng; Hongjian Zhang; Jinxing Wang (Computers and Electronics in Agriculture, 2025)

Delayed algal blooms to runoff surges in low-runoff estuaries: hydrodynamic and nutrient driving mechanisms and early warning strategies - Linlin Wang; Zuoyi Chen; Gang Wang; Yike He; Lin Mu; Xianzhong Mao; Hongsheng Bi; Jiabo Zhang (Journal of Hydrology, 2025)

An automated river shoreline space type identification method using remote sensing data that considers space-channel attention multi-scale features - Shijiao Qiao; Wanlai Xue; Kun Jia; Jie Li; Mu Xia; Zhulin Chen; Haiying Jiang; Bo Yuan; Guofeng Tao; Yuran Cui; Linlin Zhao; Zihang Jiang; et al. (International Journal of Remote Sensing, 2025)

The emulsion-filled gels with different fat contents exhibit various friction behavior and dynamic fat-related texture perception at different temperatures - Yueji Zeng; Sihan Zhang; Ke Fan; Shuo Mu; Yang Luo; Linlin Wang; Xiankang Fan; Fuqing Wang; Ran Wang; Jie Luo (Food Quality and Preference, 2025)

Oxygenated volatile organic compounds in Beijing: Characteristics, chemical reactivity, and source identification - Gen Zhang; Xiaoqi Zhou; Yifeng Sun; Chong Han; Jiyun Xian; Changxu Mu; Wanyun Xu; Linlin Liang (Environmental Pollution, 2025)

Constructing efficient lithium salt dissociation solid-state electrolytes with high conductivity and transference number of Li ions for stable all-solid-state lithium batteries - Zengcai Guo; Shimin Liao; Feng Li; Linlin Shi; Bihai Su; Jingbo Mu; Yanming Wang; Zhongkai Huang; Feng Xu; Chaowen Guan (Chemical Engineering Journal, 2024)

Different Changing Patterns of Three NOS–NO System Activities after Ischemia–Reperfusion in Rabbit with AMI - Jun Zhang; Chao Chen; Fengpeng Li; Guangren Gao; Jinguo Fu; Heping Niu; Kai Yu; Lei Wang; Run Guo; Yanfang Wan; Zhanfeng Ma; Qianyu Zhang; et al. (Cell Biochemistry and Biophysics, 2021)

Molecular Evolution of Tooth-Related Genes Provides New Insights into Dietary Adaptations of Mammals - Yuan Mu; Ran Tian; Linlin Xiao; Di Sun; Zepeng Zhang; Shixia Xu; Guang Yang (Journal of Molecular Evolution, 2021)
Mammals have evolved different tooth phenotypes that are hypothesized to be associated with feeding habits. However, the genetic basis for the linkage has not been well explored. In this study, we investigated 13 tooth-related genes, including seven enamel-related genes ( AMELX , AMBN , ENAM , AMTN , ODAM , KLK4 and MMP20 ) and six dentin-related genes ( DSPP , COL1A1 , DMP1 , IBSP , MEPE and SPP1 ), from 63 mammals to determine their evolutionary history. Our results showed that different evolutionary histories have evolved among divergent feeding habits in mammals. There was stronger positive selection for eight genes ( ENAM , AMTN , ODAM , KLK4 , DSPP , DMP1 , COL1A1 , MEPE ) in herbivore lineages. In addition, AMELX , AMBN , ENAM , AMTN , MMP20 and COL1A1 underwent accelerated evolution in herbivores. While relatively strong positive selection was detected in IBSP , SPP1 , and DSPP , accelerated evolution was only detected for MEPE and SPP1 genes among the carnivorous lineages. We found positive selection on AMBN and ENAM genes for omnivorous primates in the catarrhini clade. Interestingly, a significantly positive association between the evolutionary rate of ENAM , ODAM , KLK4 , MMP20 and the average enamel thickness was found in primates. Additionally, we found molecular convergence in some amino acid sites of tooth-related genes among the lineages whose feeding habit are similar. The positive selection of related genes might promote the formation and bio-mineralization of tooth enamel and dentin, which would make the tooth structure stronger. Our results revealed that mammalian tooth-related genes have experienced variable evolutionary histories, which provide some new insights into the molecular basis of dietary adaptation in mammals.

Effects of Vitamin E and Selenium on Growth Performance, Antioxidant Capacity, and Metabolic Parameters in Growing Furring Blue Foxes (Alopex lagopus) - Keyuan Liu; Hanlu Liu; Ting Zhang; Linlin Mu; Xueqing Liu; Guangyu Li (Biological Trace Element Research, 2019)

Analyzing Coastal Wetland Degradation and its Key Restoration Technologies in the Coastal Area of Jiangsu, China - Linlin Cui; Guosheng Li; Ninglei Ouyang; Fengyun Mu; Fu Yan; Youtian Zhang; Xiaoyang Huang (Wetlands, 2018)